1984
DOI: 10.1021/jo00183a020
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of olefins under reductive conditions. Cobalt-catalyzed selective conversion of aromatic olefins to benzylic alcohols by molecular oxygen and tetrahydroborate

Abstract: portions of water, 10% sodium thiosulfate solution, saturated sodium bicarbonate solution, and saturated sodium chloride. The organic layer was dried over anhydrous sodium sulfate, filtered, and concentrated by rotary evaporation to afford 1.11 g of a yellow oil. The oil was eluted through a silica column with dichloromethane, and the solvent was removed by rotary evaporation. Recrystallization from hot methanol afforded 480 mg (55%) of iodide 17-2-d as colorless needles: mp 47-48 °C; 0% d0, 100% di.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 4 publications
2
32
0
Order By: Relevance
“…75 This improved reaction used the cobalt(II) porphyrin, Co(TPP), as catalyst, and Et 4 NBH 4 as reductant. The catalyst hydrates aryl-conjugated alkenes in yields of 14–98% and the reactions are run for 2–10 days.…”
Section: C-o Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…75 This improved reaction used the cobalt(II) porphyrin, Co(TPP), as catalyst, and Et 4 NBH 4 as reductant. The catalyst hydrates aryl-conjugated alkenes in yields of 14–98% and the reactions are run for 2–10 days.…”
Section: C-o Bondsmentioning
confidence: 99%
“…75 Moreover, isolation of the corresponding cobalt-alkyl ( 420 ) and cobalt-peroxy ( 416 ) complexes was possible and they were tested towards the formation of the hydration product; both of them afforded 1-phenylethanol in excellent yield, which suggested that these are viable reaction intermediates. Other early examples of metal-alkyl complexes were reported in the literature in which cobalt, manganese or iron catalysts bearing electron-rich ligands were used.…”
Section: Mechanistic Overviewmentioning
confidence: 99%
“…11,12,20,21) The presence of molecular oxygen has remarkably effected the reduction of 1. As the amount of oxygen bubbled into the reaction mixture is increased, the yield of 2 is further decreased even with 1200 mmol of NaBH 4 .…”
Section: )mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Herein, we report the biomimetic reduction of 1 with sodium borohydride catalyzed by metalloporphyrins in organic solvents under anaerobic and aerobic conditions.…”
mentioning
confidence: 99%
“…Oxygenation of olefins by molecular oxygen was performed in the presence of NaBH 4 and metal catalysts such as Mn III , 177,178 Co II ,179 and Fe III (eq 42). 180,181…”
mentioning
confidence: 99%